Factors Related to the Standard Operating Procedure Compliance of the Workers at PT X - Firda Rahmawati (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: Each company has its Standard Operational Procedure that is used as a standard for workers to work safely. SOPs are established and implemented to minimize the hazards of accidents in the workplace. As one of the largest automotive manufacturing companies in Indonesia, PT X also has the potential hazards of occupational accidents. The existence of accidents at the company is caused by unsafe behavior. The purpose of this study is to analyze the correlation between individual characteristics, training, knowledge, as well as motivation and the SOP compliance at PT X. Methods: This research is observational research with the cross-sectional design. The samples of this research were 30 workers. The samples were taken by using the simple random sampling method. The data collection was obtained from the results of questionnaires, interviews, and observations, while the supporting data in the form of secondary data was taken from the related SOP. Results the variable of individual characteristics in the form of age and working period are not related to the behavior of SOP compliance. The variables of worker training, knowledge, and motivation are related to SOP compliance behavior tested with the statistical test showed the p-values of 0.008, 0.000, and 0.022. Conclusion: The individual characteristics of age and working period cannot describe the behavior of SOP compliance, while the individual characteristics of training, knowledge, and motivation can improve the SOP compliance. Keywords: motivation, SOP compliance, training